Spenser's Allegory of Justice in Book Five of the Fairie Queen - Dunseath, T. K. (Book collections on Project MUSE., 1968)
"The importance of Dunseath's study is that it proposes an original interpretation of the allegory of The Faerie Queene, Book V, and a fresh theory of its poetic function.... It brings new material into play, and offers a sensible, integrated reading of many of the poem's most important passages, so that it may well prove a pace-setter for this kind of Spenserian study."-Alastair Fowler, Brasenose College, Oxford.Originally published in 1968.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.